Inflammasome Proteins As Biomarkers of Multiple Sclerosis - Keane, Robert W.; Dietrich, W. Dalton; de Rivero Vaccari, Juan Pablo (Frontiers in Neurology, 2018)
Multiple sclerosis (MS) is an autoimmune disease that affects the brain and spinal cord. The inflammasome is a multiprotein complex that contributes to the innate immune response in animal models of MS as well as in patients with the disease. Important to the care of patients with MS is the need for biomarkers that can predict disease onset, disease exacerbation as well as response to treatment. In this study, we analyzed serum samples from 32 patients with MS and 120 age-matched controls, and provide receiver operator characteristic (ROC) curves with associated confidence intervals following analyses of serum samples from patients with MS and from the healthy unaffected donors and determine the sensitivity and specificity of inflammasome proteins as biomarkers of MS. We report that caspase-1 (1.662+/-0.6024 difference between means), apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) (407.5+/-35.79) and interleukin (IL)-18 (78.53 +-17.86) were elevated in the serum of MS patients when compared to controls. Interestingly, the levels of IL-1 (-0.5961+/-0.265) were lower in the MS cohort. Importantly, the area under the curve (AUC) for ASC and caspase-1 were 0.9448 and 0.848, respectively. Taken together, these data suggest that ASC and caspase-1 could be potential candidate biomarkers for MS onset.